ANALISIS SISTEM INFORMASI AKUNTANSI SIKLUS PENJUALAN DAN PENERIMAAN KAS TERHADAP PENGENDALIAN INTERNAL PADA PERUM BULOG KANWIL JAKARTA DAN BANTEN - Anggraeni, Noerlia; Yosepha, Sri Yanthy (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2024)
This study aims to determine the sales cycle accounting information system and cash receipts accounting information systems on internal control at the Jakarta and Banten Regional Bureau of Logistics Bureau, where it is very important for the company's progress. This research uses quantitative methods and uses primary data. The method used in data collection is by interviewing the head of operations, analyzing the data and comparing the theory with the results of the data obtained. The results of the simultaneous test analysis showed that the SIA variable of sales (X1) and SIA of cash receipts (X2) simultaneously on internal control (Y) had a positive influence and a significant relationship on the AIS cycle.Keywords: Sales, Cash Receipts, Internal Control